"An Unusual Phenomenon": The Women's Work Sub-Committee at the Imperial War Museum and how it Recorded what Women Did during the Great War. Issue 4 (December 2018) - Paterson, Sarah
The Imperial War Museum was formed in 1917 to be both a memorial to and a place of record of every type of British and Commonwealth activity that took place during the First World War. It was a total war that created massive social upheaval. Women played an increasingly active role as the war progressed, and the Women's Work Sub-Committee was established to record the female contribution. It was active primarily between 1917 and 1920 and gathered exhibits, uniforms, documents, publications, photographs, and artwork and commissioned models by female artists to demonstrate what women had done. This period coincided with the peak activity of women's work and its rapid decline, and there was a determination to ensure that what had happened would be permanently remembered. The resulting collection is unique in capturing an intense, brief period when women worked together for the common good in a national emergency. How it has been utilized, studied, and displayed over the past century is informative. After 1918, women may have reverted to domestic roles, but there was never any doubt that they were an important resource, and in 1939, there was considered no need to systematically collect material about women, as they were factored into the war effort from the start.